Two-Dimensional Direction of Arrival Estimation for Improved Archimedean Spiral Array With MUSIC Algorithm - Jin Chen; Sheng Guan; Ying Tong; Lei Yan (IEEE Access, 2018)
Direction-of-Arrival (DOA) estimation capability of sensor arrays is greatly influenced by geometric configuration of arrays. We proposed a new type 2-D planar array, improved Archimedean spiral array (IASA), to arrange sensor elements and enhance the array performance through Archimedean curves. The 2-D MUSIC algorithm is used to estimate the spatial spectrum of signals. The analysis is complemented with numerical simulations. By comparing the root mean square error, the IASA has better 2-D DOA estimation results than circular array, rectangular array, and concentric ring array.